2020
DOI: 10.3390/biom10030402
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Metabolic Lipid Mediators in the Regulation of Apoptosis

Abstract: Apoptosis is the physiological mechanism of cell death and can be modulated by endogenous and exogenous factors, including stress and metabolic alterations. Reactive oxygen species (ROS), as well as ROS-dependent lipid peroxidation products (including isoprostanes and reactive aldehydes including 4-hydroxynonenal) are proapoptotic factors. These mediators can activate apoptosis via mitochondrial-, receptor-, or ER stress-dependent pathways. Phospholipid metabolism is also an essential regulator of apoptosis, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 151 publications
(202 reference statements)
1
34
0
Order By: Relevance
“…Oxidative stress also promotes other metabolic changes, including an increase in the production of pro-inflammatory cytokines, which we and other authors previously observed in granulocytes of patients with psoriasis [ 8 , 29 , 30 ]. In addition, ROS can react with lipids, proteins and nucleic acids to modify their structure and functions, and has been observed with proteins and lipids in psoriatic blood cells [ 7 , 8 , 29 , 31 ]. This type of action is believed to lead to the exacerbation of disease symptoms [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress also promotes other metabolic changes, including an increase in the production of pro-inflammatory cytokines, which we and other authors previously observed in granulocytes of patients with psoriasis [ 8 , 29 , 30 ]. In addition, ROS can react with lipids, proteins and nucleic acids to modify their structure and functions, and has been observed with proteins and lipids in psoriatic blood cells [ 7 , 8 , 29 , 31 ]. This type of action is believed to lead to the exacerbation of disease symptoms [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…VIP values were calculated by an OPLS-DA model using the metaboanalyst software. (Sudhahar et al, 2010;Bennett and Gilroy, 2016;Figueiredo-Pereira et al, 2016;Shearer and Walker, 2018;Rahman et al, 2019;Wójcik et al, 2020). Of note, these oxylipins of AA change with the progression of ICH and the destructive oxylipins appear to peak 3 days after ICH when the protective oxylipins of AA have descended suggesting that AA-derived oxylipins tend to cause damage with the development of ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to oxylipins derived from n–3 PUFAs (DHA, EPA), those derived from n–6 PUFAs (AA, LA) generally, but not always, exhibit pro-inflammatory, vasoconstrictive, and proliferative effects ( Gabbs et al, 2015 ). In the acute phase of ICH, the increased production of LTE4, PGJ2, 5-oxo-ETE, and 15-oxo-ETE derived from AA may exhibit vasoconstrictive, pro-apoptotic, pro-inflammatory, and chemoattractant effects which are inclined to aggregate the damage of ICH, while 5,6-DiHETrE, 12-HETE, and EETs show opposing effects such as vasodilative, anti-apoptotic, or anti-inflammatory activities ( Sudhahar et al, 2010 ; Bennett and Gilroy, 2016 ; Figueiredo-Pereira et al, 2016 ; Shearer and Walker, 2018 ; Rahman et al, 2019 ; Wójcik et al, 2020 ). Of note, these oxylipins of AA change with the progression of ICH and the destructive oxylipins appear to peak 3 days after ICH when the protective oxylipins of AA have descended suggesting that AA-derived oxylipins tend to cause damage with the development of ICH.…”
Section: Discussionmentioning
confidence: 99%
“…This is important for the recognition of apoptotic cells by macrophages and their subsequent removal by phagocytosis [44]. Phospholipid metabolism is also an essential regulator of apoptosis, a highly desirable event in psoriasis to prevent the hyperproliferation of keratinocytes [45]. The process of phospholipid transformation catalyzed by cyclooxygenase and lipoxygenase leads to the generation of D-series prostaglandins and J-series prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…These mediators, through various metabolic pathways, induce apoptosis of keratinocytes [46]. Moreover, ROS-dependent lipid peroxidation end products, namely 4-HNE and 4-HHE, also induce apoptosis through their involvement in the receptor pathway of apoptosis [45].…”
Section: Discussionmentioning
confidence: 99%